Derivative of Exponential Function

From ProofWiki
Jump to: navigation, search

Theorem

Let $\exp$ be the exponential function.

Then:

$D_x \left({\exp x}\right) = \exp x$


Corollary 1

Let $c \in \R$.

Then:

$D_x \left({\exp \left({c x}\right)}\right) = c \exp \left({c x}\right)$


Corollary 2

Let $a \in \R: a > 0$.

Let $a^x$ be $a$ to the power of $x$.


Then:

$D_x \left({a^x}\right) = a^x \ln a$


Proof 1

\(\displaystyle D_x \left({\exp x}\right)\) \(=\) \(\displaystyle \lim_{h \to 0} \frac {\exp \left({x+h}\right) - \exp x} h\)          by definition of derivative          
\(\displaystyle \) \(=\) \(\displaystyle \lim_{h \to 0} \frac {\exp x \cdot \exp h - \exp x} h\)          Exponent of Sum          
\(\displaystyle \) \(=\) \(\displaystyle \lim_{h \to 0} \frac {\exp x \left({\exp h - 1}\right)} h\)                    
\(\displaystyle \) \(=\) \(\displaystyle \exp x \left({\lim_{h \to 0} \frac {\exp h - 1} h}\right)\)          Multiple Rule for Limits of Functions, as $\exp x$ is constant          
\(\displaystyle \) \(=\) \(\displaystyle \exp x\)          Derivative of Exponential at Zero          

$\blacksquare$


Proof 2

We use the fact that the exponential function is the inverse of the natural logarithm function:

$y = e^x \iff x = \ln y$
\(\displaystyle \dfrac {\mathrm d x} {\mathrm d y}\) \(=\) \(\displaystyle \dfrac 1 y\)          Derivative of Natural Logarithm Function          
\(\displaystyle \implies\) \(\displaystyle \dfrac {\mathrm d y} {\mathrm d x}\) \(=\) \(\displaystyle \dfrac {1} {1 / y}\)          Derivative of Inverse Function          
\(\displaystyle \) \(=\) \(\displaystyle y\)                    
\(\displaystyle \) \(=\) \(\displaystyle e^x\)                    

$\blacksquare$


Proof 3

\(\displaystyle D_x (\ln e^x)\) \(=\) \(\displaystyle D_x (x)\)          Exponential of Natural Logarithm          
\(\displaystyle \implies\) \(\displaystyle \frac{1}{e^x}D_x (e^x)\) \(=\) \(\displaystyle 1\)          Chain rule, Derivatives of Natural Log and Identity functions.          
\(\displaystyle \implies\) \(\displaystyle D_x (e^x)\) \(=\) \(\displaystyle e^x\)          multiply both sides by $e^x$          

$\blacksquare$


Also see


Sources